The poet as guardian of the unborn: on poetry, potentiality and love – exemplified by Nelly Sachs's poem 'Auch dir, du mein Geliebter'. Issue 5 (4th May 2021) - Boysen, Benjamin; Lose, Poul Johan
ABSTRACT: In the following we will show how a careful reading of Nelly Sachs's poetry compels a reﬂection on how love and potentiality are crucial to an understanding of the nature of poetical writing. Through a reading of Sachs's poem 'Auch dir, du mein Geliebter' ['You too, You my Beloved'] from the early collection of poems In die Wohnungen des Todes [ In the Habitations of the Dead, 1947], focusing on the Nazi genocide of the Jews, we endeavour to show how her writing, as it confronts the traumatic facticity, strives to re-inscribe the lost potentiality in the poetical universe. Sachs's painful and intense amorous discourse extracts the hymnic from the elegiac, as it, within the poetical realm, restores the existential potential of the otherwise annihilated existence. The analytical section of the article is preceded by a theoretical section, in which we develop the following thesis through readings of Aristotle, Martin Heidegger, and Giorgio Agamben: poetical writing constitutes the human being's caring interpretation of its existential potential and abilities, which, however, are non-reducible to any concrete beings or any kind of actuality or actualisation. Poetical writing is therefore to be understood as love striving to enunciate the possibility of the possible.